(untitled) (African Journal of Law and Politics, 2025)
The birth of the United Nations in 1945 continue to inspire great hope around the world. As the coner stone of universal multilateralism, this organisation established in the aftermarth of world war II emerged as a platform with the primary goal of promoting international peace and security among States. From a purly liberal perspective, it should be understood as a space for dialogue and interdependence among members states in a context of ongoing global tensions. To what extent can we affirm the importance of UN for States and relations among people ? We hypothesize that international organizations serve as functional spaces that contribute to the promotion of a share ideal among various members states. In this sense, neoliberal intitutionalism, which emphasizes interdependance among actors in international relations, proves useful for this analysis. By focussing on the United Nations, our aim is to present this universal organization as essential to cooperation and interdependent relations among states.